2015
DOI: 10.1111/dmcn.12760
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for early diagnosis of cerebral palsy from national registry data

Abstract: Aim As early intervention is important in cerebral palsy (CP), an early diagnosis is desirable. The aim of this study was to establish the median diagnostic age of CP and to identify predictors of an early diagnosis in a population‐based cohort. Method Using the Danish National Cerebral Palsy Registry (NCPR), we identified 1291 children with CP (764 males, 527 females) born between 1995 and 2003. The date of diagnosis was defined as the day the parents were told that their child was spastic or had CP. We calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 11 publications
7
56
1
3
Order By: Relevance
“…The findings are similar to a study conducted in Denmark, which showed that the mean age of diagnosis for CP, associated with the onset of symptoms such as high degree of motor disability, abnormalities on cerebral ultrasound and the presence of epilepsy, was around 11 months of age [19]. As verified in our study and reported in other studies, epilepsy is a prevalent comorbidity in patients with CP [4,[19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…The findings are similar to a study conducted in Denmark, which showed that the mean age of diagnosis for CP, associated with the onset of symptoms such as high degree of motor disability, abnormalities on cerebral ultrasound and the presence of epilepsy, was around 11 months of age [19]. As verified in our study and reported in other studies, epilepsy is a prevalent comorbidity in patients with CP [4,[19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…This lack of clinical history often leads to late diagnosis and delayed referral for intervention. A Danish register study found that ambulant children with CP are the latest to be diagnosed, particularly those with bilateral spastic CP who are a mean age of 23.9 months at diagnosis . In contrast, non‐ambulant children typically receive their diagnosis by 6 months of age.…”
Section: Clinical Scenariosmentioning
confidence: 99%
“…Preterm infants and those with encephalopathy at birth are more at risk for CP than their peers, but children without apparent risk factors can also be diagnosed with CP (Facts about Cerebral Palsy, Key Facts). The average age at diagnosis of CP varies by country and setting and is reported to be between 12 and 27 months of age (Byrne, Noritz, Maitre,, & NCH Early Developmental Group, ; Granild‐Jensen, Rackauskaite, Flachs, & Uldall, ; Hubermann, Boychuck, Shevell, & Majnemer, ; Novak et al, ). A late diagnosis may result in missed intervention opportunities for children and their families: Delays in diagnosis are associated with significant parental dissatisfaction, stress, and depression (Baird, McConachie, & Scrutton, ; Novak et al, ) and higher rates of mental health problems in children and adolescents (Whitney, Warschausky, & Peterson, ).…”
Section: Introductionmentioning
confidence: 99%